Involvement of Dynamin-Related Protein 1 in Free Fatty Acid-Induced INS-1-Derived Cell Apoptosis - Peng, Liang; Men, Xiuli; Zhang, Wenjian; Wang, Haiyan; Xu, Shiqing; Fang, Qing; Liu, Honglin; Yang, Wenying; Lou, Jinning (PLOS ONE, 2012)
Elevated extracellular free fatty acids (FFAs) can induce pancreatic beta cell apoptosis, thereby contributing to the pathogenesis of type 2 diabetes mellitus (T2D). Mitochondrial dysfunction has been implicated in FFA-induced beta cell apoptosis. However, molecular mechanisms linking mitochondrial dysfunction and FFA-induced beta cell apoptosis are not clear. Dynamin-related protein 1 (DRP-1) is a mitochondrial fission modulator. In this study, we investigated its role in FFA-induced INS-1 beta cell apoptosis. DRP-1 protein was promptly induced in INS-1 cells and rat islets after stimulation by FFAs, and this DRP-1 upregulation was accompanied by increased INS-1 cell apoptosis. Induction of DRP-1 expression significantly promoted FFA-induced apoptosis in DRP-1 WT (DRP-1 wild type) inducible INS-1-derived cell line, but not in DRP-1K38A (a dominant negative mutant of DRP-1) inducible INS-1-derived cell line. To validate these in vitro results, we transplanted DRP-1 WT or DRP-1 K38A cells into renal capsules of streptozotocin (STZ)-treated diabetic mice to study the apoptosis in xenografts. Consistent with the in vitro results, the over-expression of DRP-1 led to aggravated INS-1-derived cell apoptosis triggered by FFAs. In contrast, dominant-negative suppression of DRP-1 function as represented by DRP-1 K38A significantly prevented FFA-induced apoptosis in xenografts. It was further demonstrated that mitochondrial membrane potential decreased, while cytochrome c release, caspase-3 activation, and generation of reactive oxygen species (ROS) were enhanced by the induction of DRP-1WT, but prevented by DRP-1 K38A in INS-1-derived cells under FFA stimulation. These results indicated that DRP-1 mediates FFA-induced INS-1-derived cell apoptosis, suggesting that suppression of DRP-1 is a potentially useful therapeutic strategy for protecting against beta cell loss that leads to type 2 diabetes.